Tugas dan Kewenangan Balai Harta Peninggalan Medan dalam Melakukan Pemberesan Harta Kepailitan Debitur - Ike Oktaviani Haro Munthe; Besty Habeahan (Majelis: Jurnal Hukum Indonesia, 2025)
the duties and authorities of the Balai harta peninggalan as regulated in law Number 37 of 2004 concerning bankrupty and the civil code are to carry out a settlement of the debtor’s bankrupty assets. The main problem and this research is How the duties and authority of the Balai Harta Peninggalan in carrying out bankrupty astate clearance and what are the obstacles faced when carrying out bankrupty estate clearance?. The method used is the normative juridical-empirical method, where the data and also the information studied in this study are based on laws, books and also based on the results and discussions obtained are where the duties and authority of the Balai harta peninggalan in center in carrying out bankrupty assets are by dividing the proceeds from the sale of bankrupty assets that have been sold and distributed to creditors bassed on the possition of the creditors starting from highest to lowest, and also the obstacles faced in dealing with debtor bankrupty assets.